An energy efficient optimized cluster establishment methodology for sensor nodes in WSN - Shivshanker Biradar; T. S. Vishwanath (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The compatibility of WSN is with various applications such as; healthcare and environmental monitoring. Whereas nodes present in that network have limited ‘battery-life’ that cause difficulty to replace and recharge those batteries after deployment. Energy efficiency is a major problem in the present situation. In present, many algorithms based on energy efficiency have been introduced to improvise the conservation of energy in WSN. The LEACH algorithm improvises the network lifetime in comparison to direct transmission and multi-hop, but it has several limitations. The selection of CHs can be randomly done that doesn’t confirm the optimal solution, proper distribution and it lacks during complete network management. The centralized EE optimized cluster establishment approach (OCEA) for sensor nodes is proposed to decrease the average energy dissipation and provide significant improvement. The proposed EE WSN model with the sensor nodes is examined under a real-time scenario and it is compared with state-of-art techniques where it balances the energy consumption of the network and decreasing the cluster head number.